A statistical quality control study on Group Steel Corporation - Ang, Angela Bianca L.; Ching, Dioselle S.; Santos, Francis Harold G.; Tongco, Serafin Benedicto U. (Diliman, Quezon City College of Engineering, 2003)
Group Steel Corporation is a metal processing company that manufactures galvanized iron (GI) sheets, corrugated iron sheets and steel pipes of different gauges. The study was conducted to determine and address problems encountered by the company to reduce its percent rejection and the additional costs/lost sales that are associated with the rejects. This study will help the company improve their GI sheet production process, material yield and process capability through the application of quality control tools and techniques such as statistical process control (SPC), process capability analysis, acceptance sampling, and other techniques. Based on the Pareto chart, Process Failure Mode, Effects and Criticality Analysis of the company, the three major problems of the company are the rejection of the galvanized and corrugated sheets due to the clogging of the sheets on the galvanizing and corrugating machines, regarding of the sheets due to the presence of folds and dents and the over deposition of zinc on the galvanized sheets. It is also identified that the pitch and depth measurements of the corrugated sheets are essential qualities that the company must monitor. The rejection and regarded data of the companies are classified as attributes data or data that are not measures and are usually classified as ?go/ no go? while the thickness of the zinc coating and the pitch and depth measurements are considered as variable data since they are measurable parameters. By conducting SPC on the processes of the company, it was found out that the galvanizing and corrugating processes are out of control. This is attributed to the clogging of the sheets on the machines and presence of folds and dents. The major factors that lead to these problems are the over deposition of zinc and lack of standard operating procedures on how the processes are conducted. Recommendations are suggested to control the variability of the process such as setting a standard operating procedures with regard to the manual handling of materials and manual feeding of the sheets to the machines, putting markers on the rollers and conducting a three-factor Analysis of Variance. The company?s process in producing the corrugated sheets that adhere to the Philippine National Standards for pitch and depth was found to be out of control but capable. It is recommended to train the inspectors to measure the pitch and depth with the correct sensitivity using the company?s vernier and micrometer calipers. For the inspection of the sheets whether they are Grade A, Grade C or rejected sheets will entail 100% inspection. However, for the Triple Spot Testing that is used for the determination of the deposited zinc on the sheets and the measurement of the pitch and depth, it was suggested that the company follow a chain sampling plan. After the analysis of each problems, general recommendations were generated such as the implementation of a laboratory analysis and re-evaluation of their vendors. An Areas for Further Study was also included in the project to give the company other issues to analyze in the future.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Group Steel Corporation; Steel industry and trade; Quality control